Training effectiveness of basic technical programme at Institute Technology Aerospace, Kolej Tentera Udara - Che Zunida, Che Azmi (2019)
The role of training for improvement of skills and knowledge has long been acknowledged. Institute Technology Aerospace (ITAS), Kolej Tentera Udara (KTU) is a training centre where Royal Malaysia Airforce (RMAF) trains technicians for maintaining the aircrafts. Trainees who are exposed to effective training generally possess technical knowledge, skills and attitudes to carry out their tasks. ITAS is committed to produce trained RMAF technical personnel and continuously improve the training processes. The purpose of this study was to identify the relationship between individual factors, environment factor and employee learning factor on the training effectiveness. A total of 102 trainees of ITAS, KTU participated in the survey by filling out the study questionnaires. From 102 questionnaires that have been distributed, there are only 100 answered questionnaires were usable for data analysis, while 2 questionnaires were unusable. The Statistical Package for the Social Science version 25.0 (SPSS) approach was utilized to test the hypotheses. Regression Analysis was used to determine the strength of the relationship between dependent variable and independent variable. The result of the direct relationship between the independent variables (individual factors, environment factor and employee learning factor) and the dependent variable (training effectiveness) show that they influence training effectiveness. This research provides better understanding on training effectiveness in ITAS, KTU and potential use of findings can be used by the organization as a reference for future research.